Calcium phosphorus levels for developing boars - Greer, J.G.; Davis, Duane L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forty-two boars averaging 67 lbs. were used to study how various levels of calcium and phosphorus in their feed affected their development. Calcium-to phosphorus ratios of 1.2 to 1 were maintained in all treatment diets, which ranged from a low of .55% calcium and .45% phosphorus to a high of 1.30% calcium and 1.05% phosphorus. Seven treatment groups were replicated three times. No significant differences were observed for average daily gain, feed efficiency, carcass length, and backfat. Based on this trial, it appears that 0.55% calcium and 0.45% phosphorus is adequate for optimum growth of developing boars.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Calcium phosphorus; Boars; Growth